By Law or In Justice : the Indian Specific Claims Commission and the Struggle for Indigenous Justice. - Dickson, Jane (UBC Press, 2018)
This insider's account of the work of the Indian Specific Claims Commission takes an unflinching look at the development and implementation of Indigenous claims policy from 1991 to 2009.